Analisis Bantuan Langsung Tunai Menggunakan Narrative Policy Framework di Kelurahan Klampis Ngasem Surabaya - Emmy Dyah Rahmawati; Anggraeny Puspaningtyas; Adi Soesiantoro (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Government of Surabaya has empowered by providing Direct Cash Assistance (BLT) in accordance with the Regulations of the Mayor of Surabaya No. 130 Year 2023 on the Implementation of Direct Cash Aid to the Poor Families in the City of Surabaya through Jatim Bank and has been implemented in Klampis Ngasem Village of Surabaya, but many still do not know about the BLT of the Government of this city. As a result, the implementation of the BLT is still unclear. The research uses the Shanahan Narrative Policy Framework (NPF) Theory and descriptive qualitative methods with an approach through observations, interviews and documentation. The results of the research show that the implementation of the BLT in Klampis Ngasem Village Surabaya has been well carried out and was welcomed by the very high enthusiasm of the community. However, in Klampis Ngasem Village there is still a lack of knowledge about the BLT and the Solid Work Program because there is no socialization about it. At the micro level, societies are used to relying on help so there is no desire to be independent and difficult to move towards prosperity. At the meso level, there is still a lack of communication about the BLT of the City Government between the institutions and the related apparatus that affects public understanding. At the macro level, the lack of transparency of the data and the criteria of the recipient by the agency on the relevant apparatus. The City Government also created a culture of dependence on aid in Klampis Ngasem Village Surabaya.